Analysis of degradation in residential battery energy storage systems for rate-based use-cases. (15th April 2020) - Mishra, Partha Pratim; Latif, Aadil; Emmanuel, Michael; Shi, Ying; McKenna, Killian; Smith, Kandler; Nagarajan, Adarsh
Highlights: Residential battery energy storage's life degradation analysis framework developed. Framework integrates rate-based controls, climate, and battery chemistries/designs. Cycling characteristics of batteries with rate-based use-cases vary significantly. Life models quantify battery degradation due to diverse controls and operations. Pathways identified to improve life under rate-based usage of residential batteries. Abstract: This article examines the impact of residential battery energy storage (BES) systems' operational modes on the life (i.e. usable energy capacity) of the battery under several climatic conditions and battery chemistries. The sharp increase in residential BES installations has been a result of decreasing costs of batteries, increase in rate structures motivated applications such as solar self-consumption and time-of-use energy management, and customers purchasing these systems for backup power. While these different modes of operations provide a combination of increased bill savings, reliability of supply, and energy sustainability to the customer, their operational characteristics vary significantly between use-cases. Functional life of BES systems is known to be strongly dependent on their operating conditions. In this article, we analyze the operation of residential BES systems under different rate-based use-cases, for different battery chemistries and cell designs, and under different environmental conditions. This is conducted by simulating the control of BES operations using rate-based cycling algorithms and analyzing the prognosis of multiple battery lifetime models that consider complex nonlinear dependencies of operational stress factors such as state-of-charge, depth-of-discharge, and temperature on degradation. Significant variations in battery life are observed owing to the differences in characteristics of the uses-cases coupled with environmental conditions and battery chemistries. Such differences lead to the conclusion that choice of residential BES technologies and chemistries should account for their intended use-cases.